On the Diversity of Linguistic Data and the Integration of the Language Sciences - D’Alessandro, Roberta; van Oostendorp, Marc (Frontiers in Psychology, 2017)
An integrated science of language is usually advocated as a step forward for linguistic research. In this paper, we maintain that such an integration is premature, and cannot take place before we 14 identify a common object of study. We advocate instead a science of language that is inherently multi-faceted, and takes into account the different viewpoints as well as the different definitions of the object of study. We also advocate the use of different data sources, which, if non contradicting, can bring more solid evidence for linguistic analysis. Last, we argue that generative grammar is an important tile in the puzzle.